2023
DOI: 10.3389/fonc.2023.1145557
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pretreatment 18F-FDG PET/CT metabolic parameters in esophageal high-grade neuroendocrine carcinoma: A bicenter retrospective study

Abstract: ObjectiveThe aim of this bicentric retrospective study was to assess the prognostic value of 18F-FDG PET/CT in patients with esophageal high-grade neuroendocrine carcinoma (NECs).MethodsFrom the database of two centers, 28 patients affected by esophageal high-grade NECs who underwent 18F-FDG PET/CT before treatment were retrospectively reviewed. Metabolic parameters (SUVmax, SUVmean, tumor-to-blood-pool SUV ratio (TBR), tumor-to-liver SUV ratio (TLR), metabolic tumor volume (MTV), total lesion glycolysis (TLG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Jiang et al showed a significant association between NECs of the uterine cervix in 22 patients and the volume as well as the lesion uptake solely of the primary tumor on FDG PET and PFS, whereas SUVmax of the primary tumor was not a prognostic marker [ 26 ]. Hou et al also described a significant prognostic value of TV and TLU on FDG PET in 28 patients with esophageal NECs [ 27 ]. The fact that FDG PET was not a prognostic tool in our cohort could be due to the small sample size in which a statistical significant effect does not break through.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al showed a significant association between NECs of the uterine cervix in 22 patients and the volume as well as the lesion uptake solely of the primary tumor on FDG PET and PFS, whereas SUVmax of the primary tumor was not a prognostic marker [ 26 ]. Hou et al also described a significant prognostic value of TV and TLU on FDG PET in 28 patients with esophageal NECs [ 27 ]. The fact that FDG PET was not a prognostic tool in our cohort could be due to the small sample size in which a statistical significant effect does not break through.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the esophageal sarcomatoid carcinoma represents a large soft tissue mass with high 18 F-FDG uptake on 18 F-FDG PET/CT. However, the 18 F-FDG PET/CT findings of esophageal sarcomatoid carcinoma are similar to part of esophageal squamous carcinoma, leiomyosarcoma, or neuroendocrine carcinoma, 10–12 which are difficult to distinguish. This case indicates that the esophageal sarcomatoid carcinoma should be taken into consideration as one of the possibilities when esophageal lesions with similar 18 F-FDG PET/CT findings.…”
mentioning
confidence: 96%